Peningkatan Aktivitas Belajar Matematika Siswa Kelas V Melalui Media Papan Kantong Data di UPTD SDN Telang 2 - Febriyah Izzatur Rif'ah; Sania Br Tampubolon; Mohammad Hawaijil Asrori; Agung Setyawan (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
Mathematics learning at the primary school level often faces challenges due to abstract concepts, resulting in low student activity. This study aims to analyze the improvement of student learning activities in data presentation material through the implementation of a manipulative conventional visual medium. A Classroom Action Research design was employed in two sequential cycles at UPTD SDN Telang 2, involving 16 fifth-grade students with low engagement. Data were collected using semi-structured interviews, structured classroom observations, and field documentation. Data were analyzed using quantitative descriptive statistics to calculate activity percentages, complemented by the Miles and Huberman interactive model for qualitative field notes. The results showed a significant transition in student behavior, where classical activity indicators rose from 35% in Cycle 1 to 83% in Cycle 2. Students shifted from passive behaviors to active participation, displaying high focus and confidence. In conclusion, the application of the "Papan Kantong Data" visual medium is highly effective in improving student learning activity, proving that concrete visual aids act as essential cognitive bridges in technology-limited primary schools.